2022
DOI: 10.1049/ipr2.12569
|View full text |Cite
|
Sign up to set email alerts
|

A selective image encryption scheme using LICC hyperchaotic system

Abstract: In this paper, an improved multi‐dimensional hyperchaotic system derived from the logistic map and the ICMIC based on closed‐loop coupling (LICC hyperchaotic system) is proposed and it is used in the design of selective image encryption. The performance analysis shows that the LICC hyperchaotic system with a strong coupling degree has parameters whose value can be set more flexibly and can generate a wider and more uniform distribution of chaotic sequences. Then selective image encryption is proposed. Firstly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Step 4: Converting semi-pixels into pixels We use equation (15) to convert the semi-pixel vector into a pixel vector.…”
Section: Dynamic Semi-pixel Level Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 4: Converting semi-pixels into pixels We use equation (15) to convert the semi-pixel vector into a pixel vector.…”
Section: Dynamic Semi-pixel Level Diffusionmentioning
confidence: 99%
“…The use of the closed-loop coupling method makes it has more complex chaotic behaviors compared with the two original 1D chaos. However, its mathematical expression is too complicated [15]. To overcome the shortcomings of the above-mentioned chaotic maps, we design an improved ICMIC which can present chaotic behaviors throughout the entire control parameter range and has a very simple mathematical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Chaos has been extensively used in many research fields since Lorenz first found the chaotic attractor in 1963 [ 53 ]. In 2022, Wei et al presented an improved three-dimensional chaotic system by integrating the logistic map and the ICMIC map through a closed-loop coupling mechanism for image encryption, which is formulated as Equation ( 1 ) [ 25 ]. …”
Section: Related Workmentioning
confidence: 99%
“…Numerous routes have been taken in the design and innovation of current chaotic image encryption schemes, such as introducing and using S-box [ 5 , 6 , 7 ], Latin square [ 8 , 9 , 10 ], multiple data-level encryption operations [ 11 , 12 , 13 ], and different chaotic systems [ 14 , 15 , 16 ]. Additionally, chaotic systems can also take on various forms, such as continuous systems [ 17 , 18 ], fractional-order systems [ 19 , 20 ], complex systems [ 21 , 22 ], and discrete systems [ 23 , 24 , 25 ]. They have advantages such as pseudorandomness, synchronization, ergodicity, and extreme sensitivity to initial values and parameters, and some of these properties are beneficial for image encryption [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of energy, there are two primary types of chaotic systems in continuous autonomous systems: dissipative chaotic systems (DCS) and conservative chaotic systems (CCS). Throughout the history of chaos theory, new chaotic systems have been proposed [2][3][4] and are widely used in the field of image encryption [5][6][7] and audio&video encryption [8,9]. Since many phenomena in nature can be modeled by dissipative physical systems, most of the existing research has focused on dissipative systems, such as the classical Lorenz [10], Chen [11], and Lü system [12], and systems based on classical systems with improvements [13][14][15], while reports on conservative chaotic flows are relatively rare.…”
Section: Introductionmentioning
confidence: 99%